Annual egg productivity predicts female‐biased mortality in avian species. (1st November 2022) - Romano, Andrea; Liker, András; Bazzi, Gaia; Ambrosini, Roberto; Møller, Anders P.; Rubolini, Diego
Abstract: Among avian species, the differential cost entailed by either sex in competition for mates has been regarded as the main evolutionary influence on sex differences in mortality rates. However, empirical evidence suggests that sex‐biased adult mortality is mainly related to differential energy investment in gamete production, with a greater annual mass devoted to egg production leading to higher female mortality. We explicitly tested the generality of this pattern in a comparative framework. Annual egg production can be relatively large in some species (up to 200% of female body mass) and annual mortality is generally biased toward females. We showed that greater annual egg productivity resulted in higher mortality rates of females relative to males. Mating system was secondarily important, with species in which males were more involved in mating competition having more equal mortality rates between the sexes. However, both traits explained only a limited fraction of the interspecific variation in female‐biased mortality. Other traits, such as sexual size dimorphism and parental care, had much weaker influences on female‐biased mortality. Our results suggest that both annual mass devoted to gamete production by females and mating system contribute to the evolution of the fundamental life‐history trade‐off between reproduction and survival in avian taxa.